Characteristics and anti-radiation activity of different molecular weight polysaccharides from Potentilla anserina L - Jipeng Shi; Jie Guo; Lele Chen; Ling Ding; Haixia Zhou; Xu Ding; Ji Zhang (Journal of Functional Foods, 2023)
Potentilla anserina L polysaccharide (PAP) possesses many bioactivities. In the present study, molecular weight, monosaccharide composition, FT-IR, molecular morphology of PAPs were characterized, the result showed that Mw of PAP-1, PAP-2, PAP-3, PAP-4, and PAP-5 were 4.480 × 105 Da , 1.284 × 105 Da, 8.377 × 104 Da, 3.639 × 104 Da, 2.412 × 104 Da; PAPs were composed of Rha, Man, Glc and Gal. And then, ROS, MDA, SOD, and GSH-Px were evaluated after radiation damage by γ-rays in RAW264.7 cells. The results demonstrated that PAPs reduce ROS and MDA content, increase the activity of SOD and GSH-Px. Especially, low-molecular weight, high Gal, and low Glu content PAP-4 possessed a better anti-radiation activity. This study provides a scientific basis for the further structure–activity relationship study of PAPs.